Influence of postexercise cooling on muscle oxygenation and blood volume changes - Ihsan, M.; Watson, G.; Lipski, M.; Abbiss, C. R. (Medicine & Science in Sports & Exercise, 2013)
Purpose: The aim of this study was to investigate the effects of postexercise cold water immersion (CWI) on tissue oxygenation and blood volume changes after intense exercise.